1992
DOI: 10.1002/jcp.1041520311
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between parathyroid hormone‐stimulated cAMP and calcium increase in UMR‐106‐01 cells

Abstract: We used the osteogenic sarcoma cell line, UMR-106-01, to determine whether the rise in free cytosolic Ca2+ concentration ([Ca2+]i) and cellular cAMP following PTH stimulation are able to be regulated independently. For this purpose, we compared the effect of a PTH antagonist, stimulation of protein kinase C, augmentation by prostaglandins, and the time course of desensitization of the two cellular responses. Two x 10(-7) M of the PTH antagonist 8,18Nle 34Tyr-bPTH(3-34) amide ([Nle,Tyr]bPTH(3-34)A) was required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…No shortterm desensitization in PTH/PTHrP receptor was observed in LLCPK-1 cells. Although classic desensitization of PTH/PTHrP receptor has been reported previously (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), it required long treatment with PTH. Additionally, it was reported that different levels of expression of ␤-adrenergic receptor kinase in lung cell lines resulted in a remarkable difference in short-term desensitization of the ␤ 2 -adrenergic receptor (47).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…No shortterm desensitization in PTH/PTHrP receptor was observed in LLCPK-1 cells. Although classic desensitization of PTH/PTHrP receptor has been reported previously (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), it required long treatment with PTH. Additionally, it was reported that different levels of expression of ␤-adrenergic receptor kinase in lung cell lines resulted in a remarkable difference in short-term desensitization of the ␤ 2 -adrenergic receptor (47).…”
Section: Discussionmentioning
confidence: 95%
“…PTHrP regulates bone development and differentiation by interacting with the PTH/PTHrP receptor found on chondrocytes and bone stromal cells (3)(4)(5)(6). Binding of PTH or PTHrP to the PTH/PTHrP receptor stimulates the accumulation of several intracellular second messengers, such as cAMP and IP3 (2,7), increases the phosphorylation of the PTH/PTHrP receptor on several serine residues within its carboxylterminal tail (8,9), stimulates receptor internalization (10)(11)(12), and causes desensitization of the PTH/PTHrP receptor-second messenger system (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) It has been shown that agonist-stimulated phosphorylation of the PTH/PTHrP receptor is not dependent on PKA or PKC (9,24). Similarly, activation of PKA and PKC is neither necessary nor required for agonist-stimulated receptor internalization (12,25).…”
mentioning
confidence: 98%
“…The presence of a functional PC2 in primary cilia suggests that Ca 2ϩ enters the cell, at least in part, through ciliary channels. A functional cAMP pathway in primary cilia suggests a contribution of cAMP-mediated signals to balance and counter Ca 2ϩ surges (3,13,20) and to regulate function in this organelle by controlling the Ca 2ϩ responses, which likely contribute to microtubular stability and thus ciliary length. In summary, herein, we provide the first experimental evidence for the presence of ciliary V2R and a functional cAMP pathway in primary cilia of renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies were employed to assess which, if any, of these signal cascades induced by PTH-(1-34) is involved in the suppression of apatite production in UMR cultures. One approach employed a PTH peptide antagonist, Nle 8,18 -Tyr 34 -PTH-(3-34) amide (PTH-(3-34)), which binds to the PTH receptor with high affinity (46,47) but does not produce a cAMP response needed to activate PKA at doses up to 10 nM (43)(44)(45)(46)(47)(48)(49). When added to cultures at concentrations up to 10 nM, PTH-(3-34) did not suppress apatite deposition in UMR cultures (Fig.…”
Section: Pth-(1-34) Potently Suppresses Apatite Deposition In Umrmentioning
confidence: 99%
“…1, A and B). The 10 -20% suppression in apatite content of UMR cultures treated with a 100 nM concentration of the antagonist peptide may be the result of a slight stimulation of PKA at this high dose (43,48), a low affinity stimulation of other signaling mechanisms (44,45,49), 2 or a minor agonist contaminant in the peptide preparation (46,47). These data indicate that mere binding of ligand to the PTH receptor is not sufficient to achieve a significant inhibition of apatite deposition in UMR cultures.…”
Section: Pth-(1-34) Potently Suppresses Apatite Deposition In Umrmentioning
confidence: 99%